Hypertension and other etiological risk factors associated with the sublingual varices: A systematic review and meta-analysis - Anju James; Chandrashekar Janakiram; Vijay S. Kumar (Journal of Oral Biology and Craniofacial Research)
Objective: This review assesses the association between hypertension and other etiological risk factors associated with sublingual varices. Introduction: Hypertension, smoking, type 2 diabetes, cardiovascular disease, and denture-wearing are risk indicators for sublingual varices. A better understanding of the potential risk factors associated with sublingual varices can assist dental clinicians in identifying underlying systemic conditions that require timely and appropriate management. Methods: The search strategy aimed to retrieve both published and unpublished literature. The databases searched included PubMed, Scopus, Google Scholar, EBSCO-APA PsycInfo, Web of Science, CINAHL, ProQuest, and Shodhganga. All retrieved citations underwent screening to assess compatibility with the inclusion criteria. The methodological validity of the included studies was critically appraised using the JBI critical appraisal tool. Quantitative data were aggregated and analyzed through a meta-analysis. For dichotomous data, the effect size was presented as odds ratios. Results: Among the nine studies included in this review, eight were cross-sectional, and one was a case-control study. The total number of participants in all nine studies was 3,854, with individual survey participant numbers ranging from 151 to 1008. The methodological quality of all included studies was good. Risk factors such as history of smoking [OR 2.59 (95 % CI 1.39, 4.81), p = 0.003], hypertension [OR 4.99 (95 % CI 1.86, 13.39), p = 0.001], cardiovascular diseases [OR 6.01 (95 % CI 4.15, 8.70), p < 0.001] and denture wearing [OR 2.64 (95 % CI 1.53, 4.53), p < 0.001] were significantly associated with sublingual varices. Conclusion: Hypertension, cardiovascular disease, history of smoking and denture wearing. are the risk factors associated with sublingual varices. Systematic review registration number: PROSPERO CRD42023396643.